Humans, robots and market crashes: A laboratory study - Todd Feldman; Daniel Friedman (University of California, Economics Department, 2008)
We introduce human traders into an agent based financial market simulation prone to bubbles and crashes. We find that human traders earn lower profits overall than do the simulated agents (robots) but earn higher profits in the most crash-intensive periods. Inexperienced human traders tend to destabilize the smaller (10 trader) markets, but otherwise they have little impact on bubbles and crashes in larger (30 trader) markets and when they are more experienced. Humans' buying and selling choices respond to the payoff gradient in a manner similar to the robot algorithm. Likewise, following losses, humans' choices shift towards faster selling. There are problems in properly identifying fundamentalist and trend-following strategies in our data.
Keywords: C63; C91; D53; G10; 330; financial markets; agent-based models; experimental economics; Wertpapierhandel; Bubbles; Börsenkrise; Experimentelle Ökonomik; Theorie